Changing the π-bridge from thiophene to thieno[3, 2-b]thiophene for the D–π–A type polymer enables high performance fullerene-free organic solar cells. Issue 47 (21st May 2019) - Chen, You; Geng, Yanfang; Tang, Ailing; Wang, Xiaochen; Sun, Yanming; Zhou, Erjun
Abstract : The photovoltaic cells ofPE2 with a thieno[3, 2- b ]thiophene (TT) π bridge realized a PCE of 13.50%, obviously higher than the 10.58% PCE ofJ52-FS with a thiophene π bridge. Abstract : For photovoltaic polymers with a D–π–A backbone, there are a great deal of D and A units, but the choice of π bridge is relatively limited and thiophene (T) is still the most effective one. Here, we utilize two D–π–A polymers, J52-FS with thiophene as the π bridge andPE2 with thieno[3, 2- b ]thiophene (TT) as the π bridge, to combine with a low band-gap non-fullenereY6, respectively. The photovoltaic cells based onPE2 :Y6 can realize a PCE of 13.50%, which is obviously higher than the 10.58% PCE of theJ52-FS :Y6 analogue. Our work demonstrates that using TT as the π-bridge is a simple and promising approach to construct efficient photovoltaic polymers.